BREAK IN TWO - Summers, M. J. (London : Piatkus, 2014)
Thirty-one-year-old Claire Hatley is running from Seattle having just discovered that her live-in boyfriend has traded her in for a twenty-two-year-old hostess. Devastated and alone, Claire must make a fresh start. She answers an ad for a chef at a guest ranch just outside Colorado Springs and finds herself face to face with Cole Mitchell, quite possibly the sexiest man to ever ride a horse.
Keywords: Man-woman relationships -- Fiction; Ranchers -- Fiction. -- United States -- Colorado; Cooks -- Fiction; Sexual attraction -- Fiction; Love stories